(untitled) (Research, Society and Development, 2022)
We present an overview of how religiosity, spirituality and its relationship with health have been scientifically addressed by Collective Health, given the current challenges facing the context of mental disorders prevalent in the world. Method: using an approach that integrates bibliometrics and integral analysis, we analyzed brazilian articles about "religiosity, spirituality and health" available in 6 tradicional specialized scientific magazines that were accessible within the SCIELO data base. We selected articles that included those specific terms in the title, abstract or text. Results: From 7.843 articles analyzed, starting with the oldest edition belonging to Public Health Magazine of 1967 and ending in 2019, 37 fit the search criteria among the volumes from all magazines. Among these 37 articles, 17 are aimed at mental health, including the context of religiosity and/ or spirituality. Within these 37 articles, in 26 the authors were not specialized in collective health, but from other majors, specially psychiatry. Finally, within the 11 remaining articles, 4 written by sanitarists pointed out positive aspects of this relationship, 7 produced by humanities researchers aimed at valuing negative aspects. Given the relevance of the theme, the reasons for this gap were discussed by analyzing the scenario of challenges. Therefore, we conclude there is the need to foster studies that will capture public policies and programs directed at mental health that include the theme, which needs greater appreciation in these post-covid times.